Smart tourism technologies and tourist satisfaction: A systematic literature review and research agenda - Yee-Yann Yap; Siow-Hooi Tan; Booi-Chen Tan; Siow-Kian Tan (Acta Psychologica)
The adoption of smart tourism technologies (STTs) has been extensive and continues to grow, with increasing attention on their role in enhancing traveler satisfaction within the tourism sector. Despite the expanding body of research on STT satisfaction, a systematic literature review (SLR) synthesizing these findings remains lacking. This study presents a comprehensive SLR of satisfaction in the context of STTs in tourism. It systematically examines 88 relevant articles, classifying and analyzing them based on the types of STTs, methodologies, and theories employed. The review identifies six groups of antecedents influencing satisfaction—technological, social, psychological, behavioral, economic, and destination-related—as well as mediation and moderation relationships, perspectives, and consequences of satisfaction. Drawing from the SLR, the study proposes a conceptual framework and research agenda, emphasizing future exploration of emerging technological features, deeper investigations into antecedents, the development of innovative measurement scales, and the multidimensional nature of satisfaction.